Educational inclusion: case study of a dual exceptional student - Soares Coutinho-Souto, Waleska Karinne (2021)
Schools with an inclusive perspective are considered an efficient tool to fight the discriminatory attitudes. In the case of gifted students, there has been an interest in carrying out studies involving those who present, simultaneously to the higher abilities, behavioral, emotional and learning difficulties, a phenomenon named dual exceptionality. The purpose of this case study was to analyze the educational inclusion of a gifted student with Asperger’s disorder from the perspective of managers, teachers, mother and student himself. The educational inclusion of the participant was considered a complex and multidimensional process because it depends on the participation of the whole school community and family. It was verified that the specialized educational service favored the inclusion of the dual exceptional student.